2014
DOI: 10.1111/evo.12358
|View full text |Cite
|
Sign up to set email alerts
|

Selection for Mechanical Advantage Underlies Multiple Cranial Optima in New World Leaf-Nosed Bats

Abstract: Selection for divergent performance optima has been proposed as a central mechanism underlying adaptive radiation. Uncovering multiple optima requires identifying forms associated with different adaptive zones and linking those forms to performance.However, testing and modeling the performance of complex morphologies like the cranium is challenging. We introduce a three- Studies of morphological adaptation aim to link form (morphology) to biomechanical function, and biomechanical function to performance, or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
126
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(129 citation statements)
references
References 83 publications
3
126
0
Order By: Relevance
“…Mainland short‐faced bats exert greater bite force and consume harder fruits than all other phyllostomids (Dumont et al., ; Madrid‐Lopez, Castro‐Luna, & Galindo‐Gonzalez, ; Santana & Dumont, ; Santana et al., ). Although similar observational analyses on the islands have been lacking, the mechanical advantage—the efficiency in transfer of force from the muscles through the jaws to the food—of insular short‐faced bats is similar to that of mainland species (Dumont et al., ). Furthermore, short‐faced bats as a group have higher mechanical advantage than all other stenodermatines, the result of directional selection to maximize this trait (Dumont et al., ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Mainland short‐faced bats exert greater bite force and consume harder fruits than all other phyllostomids (Dumont et al., ; Madrid‐Lopez, Castro‐Luna, & Galindo‐Gonzalez, ; Santana & Dumont, ; Santana et al., ). Although similar observational analyses on the islands have been lacking, the mechanical advantage—the efficiency in transfer of force from the muscles through the jaws to the food—of insular short‐faced bats is similar to that of mainland species (Dumont et al., ). Furthermore, short‐faced bats as a group have higher mechanical advantage than all other stenodermatines, the result of directional selection to maximize this trait (Dumont et al., ).…”
Section: Discussionmentioning
confidence: 98%
“…Compared to all extant short‐faced bats, Cubanycteris conserves a stout and relatively long skull (at 27.5–27.8 mm it is as long as that of Artibeus jamaicensis ), with a longer rostrum. As palate width and length are the main determinants of mechanical advantage (Dumont et al., ), the longer rostrum potentially results in lower mechanical advantage compared to its close relatives. Other things being equal, lower mechanical advantage results in lower bite force (Dumont et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has suggested that bats adapt their crania in favour of mechanical efficiency of biting, whereas adaptation to cranial strength (i.e. low VM stress) is not as strongly selected for [45]. …”
Section: Discussionmentioning
confidence: 99%
“…The two primarily nectarivorous phyllostomid subfamilies, Glossophaginae and Lonchophyllinae, share adaptations for acquiring nectar including an elongated rostrum and palate, reduced dentition and elongated tongues [8][9][10]. These phyllostomids compose a phenotypic optimum that prevents eating hard foods such as beetles or figs [11][12][13]. Behavioural and dietary analyses show these bats vary in nectar specialization.…”
Section: Introductionmentioning
confidence: 99%